Effectiveness of Community-Based Programs on Aggressive Behavior Among Children and Adolescents: A Systematic Review and Meta-Analysis. - Jiang, Shan; Chen, Yinglin; Wang, Lin (Trauma, Violence & Abuse, 2024)
Adolescent aggressive behavior has increasingly become a central issue affecting the safety of both school campuses and the broader society. Despite the existence of numerous community interventions targeting this issue, there has been a paucity of efforts to consolidate the findings on the effectiveness of community-based programs in preventing aggressive behavior. This meta-analysis sought to address this gap by reviewing and assessing the impact of community-based initiatives on reducing adolescent aggression. A thorough search was carried out on 12 electronic databases: EBSCO, ERIC, PubMed, PsycINFO, MEDLINE, EMBASE, Scopus, Web of Science, ProQuest Dissertations and Theses, the China National Knowledge, Wanfang Databases, and China Science and Technology Journal Database. Sixteen studies were finalized, and meta-analyses were performed using a random effect model on RevMan v5.4 software developed by Cochrane. The analysis encompassed 16 published studies, involving a total of 2,585 participants. The key components of existing programs for aggression reduction included providing behavioral skills and training for adolescents, employing a problem-solving approach to address behavioral issues, offering psychological treatment, and emphasizing community supervision. The results indicate a significant positive effect of community-based interventions on aggression reduction (standardized mean difference = −0.26, 95% confidence intervals [−0.39, −0.13], Z = 3.84, p <.001). The subgroup analyses revealed that the intervention's effectiveness was moderated by the duration of the intervention, its theoretical foundation, and the sample size. This study furnishes empirical evidence supporting the enhancement of policies and practices to foster community engagement in mitigating aggressive behavior.